Pengaruh Model Direct Instruction Berbantuan Video Animasi terhadap Kemampuan Membaca Permulaan Siswa Kelas 2 SDN 86 Singkawang - Nata Permata; Gunta Wirawan; Wahyuni Oktavia (STIKes Ibnu Sina Ajibarang, 2026)
This study aimed to: (1) determine the initial reading ability before using the direct instruction model assisted by video animation in 2nd grade students of SDN 86 Singkawang, (2) assess reading ability after using the model, and (3) examine the effect of the model on beginning reading skills. The population consisted of 25 students in the experimental class and 25 in the control class. Data analysis included normality and homogeneity tests, T-test, correlation, and N-Gain analysis. Results showed that initial reading ability before the intervention had N-Gain scores of 9.88 for the experimental class and 11.32 for the control class, indicating differences between classes. After the intervention, N-Gain scores were 11.72 for the experimental class and 11.56 for the control class, showing a sharper improvement in the experimental class. The fun and engaging learning process increased student concentration and reduced boredom. The t-test revealed a significance value of 0.018 for the experimental class and 0.628 for the control class, indicating a significant improvement in reading ability in the experimental class, while no significant change occurred in the control class. This demonstrates the positive effect of using the direct instruction model with animated video media.